"I feel more protective over my body:" A brief report on pregnant women's embodied experiences during the COVID-19 pandemic. (September 2022) - Nolen, Erin; Siegel, Jaclyn A.; Pownall, Madeleine; Talbot, Catherine; Dann, Charlotte
Abstract: The COVID-19 pandemic has dramatically altered the experiences of pregnant people. For example, the pandemic has disrupted access to healthcare, social distancing has reduced social support, and vaccine rollout has led to safety concerns. Consistent with the Developmental Theory of Embodiment, which posits that our experiences of our bodies are influenced by social factors, studies have revealed an uptick in body dissatisfaction and disordered eating during this time. However, research on pregnant people's experiences of their body and body image during the pandemic has been largely overlooked. In this exploratory qualitative study, we aimed to broadly understand how the pandemic and quarantine have impacted the way pregnant women ( N = 190) in the US and UK relate to their bodies. We used Consensual Qualitative Research-Modified (CQR-M) to analyze pregnant women's brief textual accounts of their embodied experiences during the pandemic and identified eight core domains across the dataset. Some participants reported no change in their embodied experiences, whereas others reported accounts of appearance and weight concerns, health behavior self-judgment, gratitude for isolation, body appreciation, maternal healthcare concerns, COVID health concerns, and health and safety strategies. We conclude with implications and recommendations for supporting pregnant people and their embodied well-being during health crises. Highlights: Participants reported self-scrutiny of weight and appearance. Embodied experiences also included body appreciation. Participants were grateful for less external feedback on body. Participants emphasized increased health and safety strategies. Embodiment is linked with maternal healthcare quality.